Characterization of the emerging B.1.621 variant of interest of SARS-CoV-2 (2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) genetic diversity has the potential to impact the virus transmissibility and the escape from natural infection- or vaccine-elicited neutralizing antibodies. Here, representative samples from circulating SARS-CoV-2 in Colombia between January and April 2021, were processed for genome sequencing and lineage determination following the nanopore amplicon ARTIC network protocol and PANGOLIN pipeline. This strategy allowed us to identify the emergence of the B.1.621 lineage, considered a variant of interest (VOI) with the accumulation of several substitutions affecting the Spike protein, including the amino acid changes I95I, Y144T, Y145S and the insertion 146 N in the N-terminal domain, R346K, E484K and N501Y in the Receptor binding Domain (RBD) and P681H in the S1/S2 cleavage site of the Spike protein. The rapid increase in frequency and fixation in a relatively short time in Magdalena, Atlantico, Bolivar, Bogotá D.C, and Santander that were near the theoretical herd immunity suggests an epidemiologic impact. Further studies will be required to assess the biological and epidemiologic roles of the substitution pattern found in the B.1.621 lineage.